Periconceptional folic acid (FA) supplementation among pregnant women in Bosnia and Herzegovina: a cross-sectional study - Djedjibegovic, Jasmina; Spahić, Lejla; Marjanović, Aleksandra; Turalić, Amila; Lugušić, Aida; Šober, Miroslav (Archives of Pharmacy, 2020)
Folic acid (FA) supplementation is recommended for all women of childbearing age and pregnant women. Still, women’s adherence to these recommendations is often low. This cross-sectional survey aimed to assess FA supplementation among pregnant women in Bosnia and Herzegovina (BiH) since no such data exist to date. Data were collected by a voluntary, anonymous, self-administered internet-based questionnaire. The inclusion criteria were current pregnancy, BiH origin, and BiH residence for at least the past 5 years. The vast majority (82.1%) of women reported inadequate periconceptional FA supplementation, and only 26.9% reported supplementation during the critical period for neural tube closure. The use of a high dose (≥5 mg/day) FA beyond the first trimester was reported by 9.0% of women. Women’s age was significantly associated with adequate folic acid use for the prevention of neural tube defects (OR=1.207, p<0.05). The periconceptional FA supplementation in the studied population is suboptimal. These preliminary data call for action, especially because BiH is a lower-middle-income country without mandatory FA food fortification program. Further research on folate dietary intake and folate status in the target group, as well as possible predictors of the low prevalence of supplementation, is recommended.